CULTURE BASED TEACHING AND LEARNING FOR INDONESIAN AS A FOREIGN LANGUAGE IN YOGYAKARTA - Darmiyati Zuchdi; Nurhadi Nurhadi (Jurnal Cakrawala Pendidikan, 2019)
The practice of culture-based teaching and learning Indonesian as a foreign language (TLIFL) has not been well managed and standardized. Therefore, this study attempted to investigate TLIFL at six universities in Yogyakarta. The investigation consisted of some cultural aspects in terms of program management, learning material, learning media, teaching approaches, methods, and strategies, learning assessment, and program evaluation. The research design was a mix method design. To collect data, it used questionnaires, interviews, and observations. The data then were analysis quantitatively and qualitatively. The research results were (1) TLIFL program management had not been culture-based, (2) TLIFL learning material had not been entirely culture-based, (3) there were not enough learning media reflected on culture, (4) approaches, methods, and strategies had not used learning models including language learning, language awareness, cultural awareness, and cultural experience, (5) the assessment of culture-based learning had not been carried out with process assessment, but some have already packed it in cultural festivals at the end of the program, and (6) there was no evaluation on TLIFL programs that explicitly evaluated program achievements on aspects of  culture awareness, and experience.